2020
DOI: 10.2174/1573401314666180924123007
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Modifications in Fissure-in-ano: A Qualitative Study Based on Persian Medicine

Abstract: Background: Anal fissure (AF) is a common disease associated with severe pain and reduced quality of life. Factors related to lifestyle, including diet and bowel habits, play a pivotal role in its pathogenesis. Most of the chronic fissures are not responsive to drugs and more likely to recur. Given the significance of diet in Persian medicine (PM), investigation on physiopathology and appropriate foods can be useful for decreases in AF symptoms and consequences. Objective: This study was intended to evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…In our prospective cohort study, we found that surgeons started treatment in almost every patient (85%) with a conservative approach. The most common initial treatment was dietary modi cation due to the ease of its application and patient compliance (12). In a study assessing the Persian medical effect on ssure treatment, constipation was considered to be a cause of ssures (12) and it was therefore recommended that avoidance of some foods and commercial baked goods was potentially bene cial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our prospective cohort study, we found that surgeons started treatment in almost every patient (85%) with a conservative approach. The most common initial treatment was dietary modi cation due to the ease of its application and patient compliance (12). In a study assessing the Persian medical effect on ssure treatment, constipation was considered to be a cause of ssures (12) and it was therefore recommended that avoidance of some foods and commercial baked goods was potentially bene cial.…”
Section: Discussionmentioning
confidence: 99%
“…The most common initial treatment was dietary modi cation due to the ease of its application and patient compliance (12). In a study assessing the Persian medical effect on ssure treatment, constipation was considered to be a cause of ssures (12) and it was therefore recommended that avoidance of some foods and commercial baked goods was potentially bene cial. In contrast, our study noted the bene ts of dietary changes were correlated with stool consistency, not to any speci c food intake or avoidance.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the rich variety of medicinal preparations in Persian medicine, there has been limited research on their effectiveness and possible adverse effects [ 2 - 6 ]. Considering the increasing popularity of herbal and traditional remedies, it is necessary to evaluate the performance of these herbal therapeutic formulations and their side effects [ 7 ].…”
Section: Introductionmentioning
confidence: 99%